Role for the shoot apical meristem in the specification of juvenile leaf identity in Arabidopsis - Fouracre, Jim P. (Proc Natl Acad Sci U S A, 2019)
The extent to which the shoot apical meristem (SAM) controls developmental decisions, rather than interpreting them, is a longstanding issue in plant development. Previous work suggests that vegetative phase change is regulated by signals intrinsic and extrinsic to the SAM, but the relative importance of these signals for this process is unknown. We investigated this question by examining the effect of meristem-deficient mutations on vegetative phase change and on the expression of key regulators of this process, miR156 and its targets, SPL transcription factors. We found that the precocious phenotypes of meristem-deficient mutants are a consequence of reduced miR156 accumulation. Tissue-specific manipulation of miR156 levels revealed that the SAM functions as an essential pool of miR156 early in shoot development, but that its effect on leaf identity declines with age. We also found that SPL genes control meristem size by repressing WUSCHEL expression via a novel genetic pathway.